(untitled) (KULT_online, 2020)
This review analyses the volume Contemporary Art in Heritage Spaces, strongly evidencing the intervention of artistic practice in heritage sites. The different case studies give an insight into ways in which remaining heritage can be vivified by always new alternative stories, thereby, quoting Nick Cass, forming "a deeply ’enmeshed encounter’ between visitor, artwork and site (p.185). This review highlights the positive example of the interdisciplinary research this publication is in itself, reconsidering the boundaries of disciplines, art and narrative forms.